Engineering cell sensing and responses using a GPCR-coupled CRISPR-Cas system - Nathan H. Kipniss (Nature Portfolio, 2017)
G-protein-coupled receptors are a large and diverse group of eukaryotic membrane receptors. Here the authors couple GPCRs to dCas9 to link extracellular sensing to genome regulation.